2013
DOI: 10.1016/j.biomaterials.2012.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-coated poly α-hydroxy acid based microparticles for heterologous prime-boost adenovirus based vaccinations

Abstract: Adenoviruses show promising potential as vectors for cancer vaccines, however, their high immunogenicity can be problematic when it comes to homologous prime-boost strategies. In the studies presented here we show that heterologous prime-boost vaccinations involving ovalbumin (OVA)-antigen coated microparticles as a prime, and adenovirus encoding OVA (Ad-OVA) as a boost, were equally as effective as homologous Ad-OVA prime-boosts at generating OVA-specific CD8+ T cell responses, which translated into effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…At present, most of the nanoparticulated vaccine formulations are designed following two strategies: the antigens are either encapsulated in nanoparticles (NPs) or displayed on the surface of NPs. It was reported that the antigen encapsulated in NPs by the self-assembly process induced a stronger antigen-specific immune response than the soluble antigen. , More recently, the applications of antigen-on-nanoparticle surface formulations, such as virus-like particles or protein particles, has become increasingly attractive, with numerous studies demonstrating that APC engagement with nanoparticles themselves triggers inflammatory responses. …”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the nanoparticulated vaccine formulations are designed following two strategies: the antigens are either encapsulated in nanoparticles (NPs) or displayed on the surface of NPs. It was reported that the antigen encapsulated in NPs by the self-assembly process induced a stronger antigen-specific immune response than the soluble antigen. , More recently, the applications of antigen-on-nanoparticle surface formulations, such as virus-like particles or protein particles, has become increasingly attractive, with numerous studies demonstrating that APC engagement with nanoparticles themselves triggers inflammatory responses. …”
Section: Introductionmentioning
confidence: 99%
“…Many types of vaccine vectors have achieved varying degrees of scrutiny in the tumor immunology field and each have their advantages and disadvantages relating to issues of safety, patient compliance, financial cost, immune potency and labor intensiveness [34, 35]. Delivery of vaccines using attenuated viruses encoding tumor antigen can be a highly efficient way of generating antitumor cellular immune responses, however, such vaccines may be prone to inducing unwanted immune responses or be neutralized by the host’s own antibodies [5, 3639]. Delivery of antigen complexed with alum tends to favor antibody responses at the expense of cellular immune responses and thus is considered unsuitable for use in cancer vaccines [40].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these vaccines have several limitations. For example, adenovirus vector-based vaccines are ineffective at inducing adenovirus-specific antibodies following the first dose ( 40 ). Subunit vaccines require adjuvants to elicit immune responses ( 41 , 42 ) because intranasal administration of antigens alone does not elicit antigen-specific antibodies.…”
Section: Introductionmentioning
confidence: 99%